The Pantun Pitutur Song: A Study of Educational Values in The Music Show of The Marawis Suma Budhaya Group - Sulaksono, Projo; Sumaryanto Florentinus, Totok; Wadiyo, Wadiyo (Catharsis, 2020)
This study aims to analyze the educational values of that is implemented through the process of interaction in the musical play of the "Pantun Pitutur" song in the Suma Budhaya group performance. This study used a qualitative method with an interdisciplinary approach to sociology and education. The data were collected by using observation, interview, and document study techniques. The data analysis procedures used data reduction, data presentation, and data verification. The validity of the data used were triangulation, data sources, and theory. The results showed that in the musical play "Pantun Pitutur" there was a process of social interaction among fellow musicians, musicians with the Suma Budhaya group, and the Suma Budhaya group with the community. Social interaction occurs through communication and social contact symbolically by using language, signs, and body language. Social contact in this performance is primary and positive. The social interaction process that was impledmented contains several educational values to the community. The educational values include; 1). Religious Value; 2). Cooperation Value; 3). Pluralist Value; and 4). Responsibility Value. The results of this study can be used as a reference regarding the study of educational values.